The Relationship of Neutrophil-Lymphocyte Ratio and Glycemic Control in Type 2 Diabetes Mellitus Patients - Nurahmi Nurahmi; Budi Mulyono; Windarwati Windarwati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Progressivity of type 2 Diabetes Mellitus (DM) is associated with a condition of chronic inflammation. The Neutrophil-Lymphocyte Ratio (NLR) has become a potential new marker of inflammation to detect chronic inflammation. This research aimed to determine NLR differences between controlled type 2 DM and uncontrolled type 2 DM groups. This research conducted an observational with a cross-sectional approach to 56 patients with type 2 diabetes. The identity, anthropometric measurements, and laboratory data of routine blood exam and HbA1c were carried out on each research subject, and then the NLR calculations were performed. The subjects were 20 (35.70%) controlled type 2 DM patients, 36 (64.30%) uncontrolled type 2 DM patients, consisting of 36 (64.30%) male and 20 (35.70%) females. The NLR value was statistically significantly higher in uncontrolled type 2 DM patients than controlled type 2 DM patients, which was 1.90±0.84 compared to 1.52±0.50 (p=0.035). There was a significant difference in the NLR value between the uncontrolled type 2 DM group and the controlled type 2 DM group.